Pengaruh Persepsi Kualitas Produk Dan Kualitas Layanan Terhadap Keputusan Pembelian Pada Platform E-Commerce Shopee Di Era Pandemi (Studi Mahasiswa Fakultas Ekonomi dan Bisnis, Universitas Islam Malang) - Achmad Syukron Chalim; Hadi Sunaryo; Eka Farida (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstrackThe shift of offline product marketing to online of course affects the level of consumer purchasing decisions for a product or service. Especially since the enactment of the appeal to stay at home to prevent and break the chain of the spread of Covid-19 in the pandemic era. This will certainly affect individual decisions in making purchase transactions. The factors that influence purchasing decisions are perceptions of product quality and service quality.The purpose of this study is to analyze and find out how much influence the perception of product quality and service quality has on purchasing decisions on the shopee e-commerce platform in the pandemic era. This research method uses a quantitative method that uses regression as a measure of how much influence the independent variable has on the dependent variable. The sample used in this study as many as 76 respondents, data collection techniques using questionnaires, data analysis using validity and reliability tests, and hypothesis analysis using t test (partial), F test (simultaneous), multiple linear regression analysis, and coefficient of determination with SPSS 20 support.The results of this study are 1) the perception of product quality and service quality simultaneously affect the purchasing decision 2) The variable perception of product quality partially affects the purchasing decision. 3) The variable perception of product quality partially influences purchasing decisions, has been partially tested Keywords: Influence, Perception of product quality, Service quality, Purchase decision